1992
DOI: 10.1002/jmv.1890370305
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation and persistence of hepatitis A virus in mussels

Abstract: Accumulation and persistence of hepatitis A virus (HAV) in the mussel Mytilus chilensis was evaluated. Under optimal filtration activity of mussels (temperature 12 degrees C, salinity 3%, feeding twice a day with Dunaliella marina), HAV was concentrated 100-fold from the surrounding water. Similar concentrations of HAV were reached in the filtration apparatus and in the digestive system (hepatopancreas). HAV persisted for about 7 days in mussels. Elimination of HAV from mussels was slower than elimination of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(28 citation statements)
references
References 17 publications
2
26
0
Order By: Relevance
“…In contrast, mussels subjected to depuration for 96 h exhibited 98.7 and 97.0% reductions in infectious HAV and rotaviruses, respectively (Abad et al 1997). In two other studies on mussels, HAV persisted for 7 days (Enriquez et al 1992), and at least 5 days (De Medici et al 2001). Ueki et al (2007) compared the persistence of human NoV and the surrogate FCV in the digestive diverticula of the oyster after depuration for 10 days and concluded that FCV was rapidly depleted, whereas NoV persisted.…”
Section: Shellfish Depurationmentioning
confidence: 86%
“…In contrast, mussels subjected to depuration for 96 h exhibited 98.7 and 97.0% reductions in infectious HAV and rotaviruses, respectively (Abad et al 1997). In two other studies on mussels, HAV persisted for 7 days (Enriquez et al 1992), and at least 5 days (De Medici et al 2001). Ueki et al (2007) compared the persistence of human NoV and the surrogate FCV in the digestive diverticula of the oyster after depuration for 10 days and concluded that FCV was rapidly depleted, whereas NoV persisted.…”
Section: Shellfish Depurationmentioning
confidence: 86%
“…Although direct studies comparing the abilities of different viruses to persist within hemocytes have been limited, a review of the literature indicates that certain viruses remain infectious within oyster tissues for extended periods, while other viruses decline more rapidly. For example, Enriquez et al (15) demonstrated that HAV persisted longer than PV in mussels. Bosch et al (6) demonstrated that within contaminated mussels, PV and adenovirus 40 had 2.7-and 3.0-log 10 reductions after depuration for 48 h, while a 96-h depuration period reduced bacteriophage B40-8, HAV, and rotavirus serotype 3 less than 2 log 10 .…”
Section: Discussionmentioning
confidence: 99%
“…Although less than 10% of the cases of hepatitis A in the United States are associated with food-borne outbreaks (7), substantial costs are incurred by both society and the food industry as a result of these outbreaks (11). The foods implicated in these outbreaks include shellfish (13,14,18,22,28,31), sandwiches, dairy products, baked products, salads, fruits, and vegetables (9, 15). Examples of such outbreaks include the outbreak in Denver, Color., in 1992, in which more than 5,000 individuals were exposed to hepatitis A virus (HAV) due to consumption of a variety of gourmet foods prepared by an infected food handler (11).…”
mentioning
confidence: 99%